Il Medioevo come storia inventata: falsi, ucronie e "mappae mundi" (Doctor Virtualis, 2021)
Analysing an historical period, such as the Middle Ages, or a more recent era, through its narration, must take into consideration many heterogeneous sources, whose form is not always immediately identifiable. In some cases, scholars may even have a secondary interest in a specific historical document, preferring to study the motivations and context behind its creation and conservation of historical testimony, either written, spoken or iconographic.Interpreting the past opens up different perspectives: is it possible to determine a single narrative genre able to describe the Middle Ages better than others? In what sense does a historical source (a forgery, a biography or a counter-factual description) enrich our knowledge of the historical past? Does it make sense to include in the study of history, sources that are not strictly textual or iconographic, such as a geographical map?Reflecting on these questions reveals an invented aspect of the Middle Ages, a fictional portrait that not only brings into view history’s shadow but also complements it.